Hospitability of ornamental and medicinal plants to root-knot nematode (Meloidogyne incognita) race 2 - Moreira, Francisco José Carvalho; Santos, Carmem Dolores Gonzaga; Silva, Gilson Soares da; Innecco, Renato (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The correct identification of species and genus of nematodes that affect a particular culture is of great importance to form a quantity of information that will be useful to laboratories for diagnosis and control of these pathogens. Because of the increase in the production of ornamental and medicinal plants in the of Cear. á State, the agricultural importance of the genus Meloidogyne and the scarcity of information on the hospitability this pathogen in these species, in that it was to evaluate the susceptibility testing of 30 species, and 20 ornamental (Antirrhimum majus, Gazania ringens, Carthamus tinctorius, Bryophyllum cayicinum, Ceasalpinia pulcherrima, Thumbergia alata, Petunia hibryda, Exacum affine, Catharanthus roseus, Opuntia sp., Sansevieria trifasciata, Asparagus densiflorus, Hibiscus mutabilis-roreus, Impatiens balsamiana, Celosia spicata, Antirrhimum sp., Dianthus chinensis, Zinnia elegans, Tagetes patula, Capsicum annuum) and 10 medicinal (Peumus boldus, Ocimum gratissimum, Mentha arvensis var. piperascens, Mentha x Vilosa, Plectranthus amboinicus, Ocimum bassilicum, Rosmarinus officinalis, Cymbopogon citratus, Lippia alba, Cymbopogon winterianus. The test was conducted in a greenhouse, of the Phytosanitary Sector, Department of Plant Science, Federal University of Ceará. The inoculation was conducted with 4,000 eggs/J2 for pot. Evaluation of the plants gave to 60 days after inoculation. Evaluated is the reaction of the plants, measuring up: number of galls and eggs, egg mass index, reproduction factor and reduce the reproduction factor. From these variables it was classified the reaction of plants to the nematode by means of five criterions. Of ownership of the results, it was verified that of the ornamental plants only species T. patula didn’t presented galls in your root system. Concerning medicinal species M. vilosa, C. citrates, L. alba, C. winterianus and P. boldus showed no galls in their root systems. Thus, concluded that the ornamental plants can contribute to the introduction of the knot nematode in areas on a presence, except T. patula. Concerning medical, it was observed behavior distinct, with five species non-host and the other medium capable, few galls, or females isolated from their roots.